Determinan Faktor Perilaku Hidup Bersih dan Sehat (PHBS) pada Keluarga Balita di Desa Jabung Kabupaten Ponorogo - Anindita Hasniati Rahmah; Lina Alfiyani (Jurnal Anestesi, 2026)
Clean and Healthy Living Behavior CHLB is an important effort to improve community health status especially among families with toddlers. Poor implementation of CHLB may increase the risk of various health problems including infectious diseases and diarrhea. The roles of community leaders and health workers are external factors that can influence the successful implementation of CHLB within families. This study aimed to analyze the relationship between the roles of community leaders and health workers and Clean and Healthy Living Behavior among mothers of toddlers. The study employed an analytical observational design with a cross sectional approach. Data were collected using a structured questionnaire and analyzed through univariate and bivariate analyses using the Chi Square test with a significance level of 0.05. The results showed that most respondents demonstrated good CHLB practices 84.0 percent, were of productive age 70.0 percent, had a moderate educational level 52.0 percent, perceived community leaders as having a good role 60.0 percent, and perceived health workers as having a good role 76.0 percent. Bivariate analysis revealed a significant relationship between the role of community leaders and CHLB with a p value of 0.002 and between the role of health workers and CHLB with a p value of 0.001. Mothers who received support from community leaders and health workers were more likely to practice clean and healthy living behaviors than those who did not receive such support. In conclusion the roles of community leaders and health workers are significantly associated with the implementation of Clean and Healthy Living Behavior among mothers of toddlers. Therefore increasing the involvement of community leaders and strengthening the role of health workers through continuous education health promotion and community assistance programs are necessary to improve clean and healthy living behaviors in the community.